Investigation of maximum overheating device dependence on its size and installation density - Семенець, В. В.; Semenets, V. V.; Sinotin, A.; Sotnik, S. (ХНУРЕ, 2020)
The theses show the results of influence studies of heated zone volume of an electronic device on its maximum overheating.
Keywords: heated zone; heat sinks; thermal conductivity; anisotropy